2020
DOI: 10.20525/ijfbs.v9i1.634
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Impacts of Operational Risk Management Practices on Banks’ Financial Performance: Study of Selected Commercial Banks in Nigeria

Abstract: Increase in losses borne by banks as a result of inadequate operational risk management practices and the adverse impact on banks’ financial performance has been a major concern to bank management and regulators. This study analysed the impact of operational risk management practices on the financial performance of commercial banks in Nigeria. 10-years (2008 - 2017) secondary data extracted from audited financial statements of selected commercial banks in Nigeria was used for the study. The data was analysed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Even though substantial effort has been made in the studies to illustrate the operational, credit, and interest risk exposures effect on financial performance and their various measures or indicators, there is an open acknowledgment that inconsistencies exist regarding the findings. For instance, he effect of liquidity risk exposure on financial performance (Waleed et al, 2016;Salim& Bilal, 2016), operational risk exposure on financial performance (Arhenful et al, 2019;Oye, 2020), credit risk exposures on financial performance (Rasika&Sampath, 2015;Kalu et al, 2017), and interest rates risk exposures on financial performance (Musah et al, 2018;Jui et al, 2020). Moreover, most of the studies identified on financial risk exposures have focused on the financial performance of commercial banks internationally (Rasika&Sampath, 2015;Waleed et al, 2016;Kostikov et al, 2019;Jui et al, 2020), regionally (Hakimi&Zaghdoudi, 2017Nwanna&Oguezue, 2017;Kalu et al,2017;Oye, 2020), and locally (Njeri, 2016;Siminyu et al, 2017;Wambari&Mwangi, 20 studies, most of the measures used are related to banking activities.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though substantial effort has been made in the studies to illustrate the operational, credit, and interest risk exposures effect on financial performance and their various measures or indicators, there is an open acknowledgment that inconsistencies exist regarding the findings. For instance, he effect of liquidity risk exposure on financial performance (Waleed et al, 2016;Salim& Bilal, 2016), operational risk exposure on financial performance (Arhenful et al, 2019;Oye, 2020), credit risk exposures on financial performance (Rasika&Sampath, 2015;Kalu et al, 2017), and interest rates risk exposures on financial performance (Musah et al, 2018;Jui et al, 2020). Moreover, most of the studies identified on financial risk exposures have focused on the financial performance of commercial banks internationally (Rasika&Sampath, 2015;Waleed et al, 2016;Kostikov et al, 2019;Jui et al, 2020), regionally (Hakimi&Zaghdoudi, 2017Nwanna&Oguezue, 2017;Kalu et al,2017;Oye, 2020), and locally (Njeri, 2016;Siminyu et al, 2017;Wambari&Mwangi, 20 studies, most of the measures used are related to banking activities.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…For instance, he effect of liquidity risk exposure on financial performance (Waleed et al, 2016;Salim& Bilal, 2016), operational risk exposure on financial performance (Arhenful et al, 2019;Oye, 2020), credit risk exposures on financial performance (Rasika&Sampath, 2015;Kalu et al, 2017), and interest rates risk exposures on financial performance (Musah et al, 2018;Jui et al, 2020). Moreover, most of the studies identified on financial risk exposures have focused on the financial performance of commercial banks internationally (Rasika&Sampath, 2015;Waleed et al, 2016;Kostikov et al, 2019;Jui et al, 2020), regionally (Hakimi&Zaghdoudi, 2017Nwanna&Oguezue, 2017;Kalu et al,2017;Oye, 2020), and locally (Njeri, 2016;Siminyu et al, 2017;Wambari&Mwangi, 20 studies, most of the measures used are related to banking activities. This indicates that further examination is necessary to not only establish the effect of financial risk exposures in other segments of the economy but also to es financial risk measures or indicators.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…These losses ultimately have both financial and non-financial implications on banks. Though several investigations had been conducted which established the impact of operational risk on the performance of banks including studies done by Bekele (2015), Muriithi (2016), Ng'aari (2016), Simamora and Oswari (2019), Fadun and Oye (2020), there are however few examining the main drivers of this risk. Ordinarily, one would have expected that factors such as; availability of historical information on operational loss events, proliferation of operational risk management practices and the stiff penalties imposed for not complying with applicable regulatory directives would have reduced the frequency…”
Section: Introductionmentioning
confidence: 99%
“…These losses ultimately have both financial and non-financial implications on banks. Though several investigations had been conducted which established the impact of operational risk on the performance of banks including studies done by Bekele (2015), Muriithi (2016), Ng'aari (2016), Simamora and Oswari (2019), Fadun and Oye (2020), there are however few examining the main drivers of this risk. Ordinarily, one would have expected that factors such as; availability of historical information on operational loss events, proliferation of operational risk management practices and the stiff penalties imposed for not complying with applicable regulatory directives would have reduced the frequency at which large operational risk events crystallizes, current realities however indicates otherwise.…”
Section: Introductionmentioning
confidence: 99%